Exploring Countermeasures to Enhance the Safety of Water Quality in Urban Water Supply (Journal of Global Humanities and Social Sciences, 2025)
The safety of water quality in China's urban water supply has always been the focus of attention from all walks of life, and the study and analysis of strengthening the safety of water quality in the urban water supply are to ensure that the quality of life in China's cities and towns is improved as well as the safety of people's lives and health. At present, many cities and towns in China have water quality problems, bringing a great impact on people's lives. Therefore, this paper studies the safety of water quality in towns and cities firstly analyses the main factors affecting the safety of drinking water quality, and then proposes some corresponding measures to solve the current situation. It is hoped that the study of this paper can bring some degree of help to China's urban water supply management.